Development of orthophosphate and silica treatments for the management of environmental contaminants at Wilkes landfill, East Antarctica - Camenzuli, Danielle (Macquarie University, 2022)
Wilkes Station is an abandoned research station located on Clark Peninsula, East Antarctica that was constructed by the United States of America during the International Geophysical Year (1957-1958). In 1961, exclusive control of Wilkes Station transferred to the Australian National Antarctic Research Expeditions. Wilkes Station was abandoned by Australia in 1969, but was not completely decommissioned due to logistical constraints. Consequently the majority of buildings, equipment and a landfill remain on-site. Annex III of the Madrid Protocol (1998) establishes the requirement for all past and present work sites in Antarctica to be cleaned up by the generators and users of sites. In response, various remediation technologies are being adapted or developed for use at contaminated sites in Antarctica and are effective, despite the challenges associated with operating in remote, cold regions. Orthophosphate and silica treatments are two technologies that demonstrate significant potential for use at Wilkes Station and other contaminated sites in Antarctica. However, their application in areas of freezing ground remains understudied. This study assessed the performance of orthophosphate, silica and coupled orthophosphate-silica treatments on metal contaminated soil and soil co-contaminated with metals and petroleum hydrocarbons to evaluate their suitability for the management of environmental contaminants at Wilkes Station. The results of four experiments indicate that silica treatments are effective at immobilising Cr, Fe, Ni, Cu, Zn, Cd, Pb, while orthophosphate and coupled-orthophosphate treatments effectively immobilise Fe, Cu, Zn, Cd and Pb, but are ineffective at immobilising Cr and Ni. None of the assessed treatments were effective at immobilising As, and concentrations of P remained above environmentally safe levels in soils where treatments containing orthophosphoric acid or triple superphosphate were applied. The formation of brushite, cattite, hydroxylapatite, hydroxypyromorphite, sodium aluminosilicates and other calcium bearing minerals following treatment with orthophosphate, silica and coupled orthophosphate-silica provided further evidence of immobilisation. Silica treatments were ineffective at reducing the mobility of petroleum hydrocarbons to environmentally safe levels in soil. Therefore, further research to optimise treatments is required before managing soil co-contaminated with metals and petroleum hydrocarbons using this technique can be considered viable. For effective management of environmental contamination at Wilkes Station, coupling the application of a chemical treatment with a downstream permeable reactive barrier capable of treating petroleum hydrocarbons, As and P contaminated water is recommended. A thorough monitoring program for detection of adverse effects of treatment and the potential for re-solubilisation of metals is also recommended.